Chapter 23 Educational Methods Using Intergenerational Interaction to Fight Ageism (2018)
Contemporary societies allow interactions between three or more generations at the same time. However, the emergence of multigenerational societies does not necessarily guarantee the eradication of ageism or age-related stereotypes. In this new social landscape, the civic mission of higher education includes the expansion of the educational toolbox for future professionals with instruments devoted to improve communication between generations. In this chapter, we refer to the intergroup contact theory, which supports intergenerational contact between young and old, not as individuals of different ages who coincide in chronological time, but as members of a community from different generations, as it is framed in the generational intelligence educational model. After presenting the theoretical background, a particular intergenerational service learning methodology is proposed and a case study, developed at Fontys University of Applied Sciences and Summa College in Eindhoven is described. This methodology is based on instructing students, not only on technical contents of a discipline but also on developing communication skills between generations. This communication tries to empathize with the ideas, interests and feelings of other generations, potentially leading to a reduction of prejudice. The chapter ends with limitations and future proposals related to generational education as an effective tool against ageism.